(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
In this article, I propose placing the attention economy at the center of communicative analysis for one simple reason: it is impossible to conceive of expression, dialogue, (mis)information, and other communicative phenomena without understanding algorithmic attention in the digital society. Attention is an essential capacity of the human mind and of any act or fact of communication. Communication requires the existence, however brief, of a community of interlocutors or sources/receivers. Any type of communication, format, or intention demands attention; otherwise, it has no reach or impact. It is impossible to persuade distracted or inattentive audiences who ignore or avoid messages. Without audiences, even if they are only minimally attentive, none of these actions are effective. Without attention, expression is pure expression—a manifestation of ideas, feelings, sensibilities—but not necessarily communication, as it has no audience or interlocutors. For communication to exist, attention is needed.